Resenha: FERREIRA, Paulo Rogers. OS AFECTOS MAL-DITOS: o indizível nas sociedades camponesas. São Paulo: Hucitec, 2008. - Silva, Rusvenia Luiza Batista Rodrigues da (Revista Campo-Território, 2012)
Resenha: FERREIRA, Paulo Rogers. OS AFECTOS MAL-DITOS: o indizível nas sociedades camponesas. São Paulo: Hucitec, 2008.